ANALISIS KEBIJAKAN PEMERINTAH POLANDIA DALAM MENGHADAPI IMIGRAN ILEGAL TAHUN 2021-2024 - Reindhard Juliantonius Simamora; Tuah Kalti Takwa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study analyzes the policies of the Polish government in addressing irregular migration during the period 2021–2024. The main focus of this research is to understand how Poland responds to the increasing flow of migrants, particularly those involving illegal entry and illegal stay. This period is significant due to the rise in migration pressure, especially following the Poland–Belarus border crisis in 2021. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through literature review, including official documents from the Polish government, European Union reports, and publications from international organizations. The analysis examines the relationship between migration dynamics and the policies implemented by the Polish government. The findings show that Poland has adopted relatively restrictive policies in dealing with irregular migration, such as strengthening border control, building physical barriers along its borders, and rejecting the European Union’s migrant relocation mechanism. These policies are largely based on considerations of national security, state sovereignty, and domestic political pressures.obstacles. Keywords: Migration policy, Irregular migration, National security